Matéria orgânica do solo em rotações de culturas sob sistema semeadura direta - Raphael, Juan Piero Antonio [UNESP] (2014)
Soil organic matter (SOM) plays major functions in agricultural soils, and its contents and quality can be altered by crop rotations and soil management. The aim of this study was to evaluate changes in soil organic matter as affected by crop rotations under no-tillage system. The study was carried out at two no-till managed field sites for at least eight years, in Botucatu, SP, Brazil. In the first experiment, the soil was a Rhodic Ferralsol, in which grain-sorghum (Sorghum bicolor (L.) Moench) and ruzigrass (Urochloa ruziziensis (R. Germ. and C. M. Evrard) Crins), single or intercropped in the fall/winter period, were the plots. Pearl millet (Pennisetum glaucum L.), forage sorghum (Sorghum bicolor (L.) Moench) and sunn hemp (Crotalaria juncea L.) were cropped in the spring, as subplots, before the summer crop (soybean). In the second experiment, the soil 4 was a Typic Rhodudalf under no-till since 2003 and the crop rotations studied were: triticale (X Triticosecale Wittmack) and sunflower (Helianthus annuus L.) as autumn-winter crops (plots); pearl millet, forage sorghum, sunn hemp and chiseling (performed in 2003 and 2009) in spring as subplots, before the summer crop (soybean). Organic matter humification degree (HLIF) was determined by laser-induced fluorescence spectroscopy (LIF) in soil samples collected from 0-0,10; 0,10-0,20; 0,20-0,40 and 0,40-0,60 m depths in April 2012. Soil aggregates stability was assessed from soil samples collected from 0-0,10 and 0,10-0,20 m depths in November 2012. The remaining soil organic matter assessments were carried out from samples collected in April 2013. Total organic carbon (TOC), total nitrogen (TN), particulate organic carbon (POC), and mineral associated organic carbon (MOC) contents were determined from soil samples collected from 0-0,10; 0,10-0,20; 0,20-0,40 and 0,40-0,60 m depths; soil microbial biomass C and N were determined from soil samples coll ...